Mercury, Lead, Cadmium, Arsenic, Chromium and Selenium in Feathers of Shorebirds during Migrating through Delaware Bay, New Jersey: Comparing the 1990s and 2011/2012 - Joanna Burger; Nellie Tsipoura; Lawrence Niles; Michael Gochfeld; Amanda Dey; David Mizrahi (Toxics, 2015)
Understanding temporal changes in contaminant levels in coastal environments requires comparing levels of contaminants from the same species from different time periods, particularly if species are declining. Several species of shorebirds migrating through Delaware Bay have declined from the 1980s to the present. To evaluate some contaminants as cause for the declines, we examine levels of mercury, lead, cadmium, arsenic, chromium and selenium in feathers of red knot (Calidris canutus, N = 46 individuals), semipalmated sandpiper (Calidris pusilla, N = 70) and sanderling (Calidris alba, N = 32) migrating through Delaware Bay, New Jersey, USA, from 1991 to 1992 (N = 40), 1995 (N = 28), and 2011–2012 (N = 80) to determine if levels have changed. We found: (1) arsenic, chromium, and lead increased in red knot and decreased in semipalmated sandpiper; (2) cadmium decreased in semipalmated sandpipers; (3) mercury decreased in red knot and sanderlings; (4) selenium decreased in red knot and increased in semipalmated sandpipers. In 2011/2012 there were significant interspecific differences for arsenic, mercury and selenium. Except for selenium, the element levels were well below levels reported for feathers of other species. The levels in feathers in red knots, sanderling, and semipalmated sandpipers from Delaware Bay in 2011/2012 were well below levels in feathers that are associated with effect levels, except for selenium. Selenium levels ranged from 3.0 µg·g−1 dry weight to 5.8 µg·g−1 (semipalmated sandpiper), within the range known to cause adverse effects, suggesting the need for further examination of selenium levels in birds. The levels of all elements were well below those reported for other marine species, except for selenium, which was near levels suggesting possible toxic effects.